2017
DOI: 10.1142/s0218271817500146
|View full text |Cite
|
Sign up to set email alerts
|

A family of Finch and Skea relativistic stars

Abstract: Several new families of exact solution to the Einstein-Maxwell system of differential equations are found for anisotropic charged matter. The spacetime geometry is that of Finch and Skea which satisfies all criteria for physical acceptability. The exact solutions can be expressed in terms of elementary functions, Bessel functions and modified Bessel functions. When a parameter is restricted to be an integer then the special functions reduce to simple elementary functions. The uncharged model of Finch and Skea … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 24 publications
(32 reference statements)
2
23
0
Order By: Relevance
“…• It is worthwhile to note that our class of solutions is similar to the family of solutions obtained by Maharaj et al (2016) even though the methods adopted are different. Maharaj et al (2016) have generated solutions to the master differential equation in terms of the Bessel functions which have later been expressed in closed forms for some specific range of model parameters defining the electromagnetic field and anisotropy.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…• It is worthwhile to note that our class of solutions is similar to the family of solutions obtained by Maharaj et al (2016) even though the methods adopted are different. Maharaj et al (2016) have generated solutions to the master differential equation in terms of the Bessel functions which have later been expressed in closed forms for some specific range of model parameters defining the electromagnetic field and anisotropy.…”
Section: Discussionmentioning
confidence: 91%
“…Maharaj et al (2016) have generated solutions to the master differential equation in terms of the Bessel functions which have later been expressed in closed forms for some specific range of model parameters defining the electromagnetic field and anisotropy. In our work, we have utilized the Frobenius method to solve the master differential equation and showed that similar class of solutions could be obtained by terminating the series solution for a specific range of anisotropy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Linear relationships involving radial pressure and the energy density exist in anisotropic stellar models of Mafa Takisa et al [20], Sunzu et al [21,22] and Kileba Matondo and Maharaj [23]. Recently, a new approach with anisotropic pressure has been investigated with the Finch and Skea geometry by Maharaj et al [24] and Kileba Matondo et al [25].…”
Section: Introductionmentioning
confidence: 99%